Tailoring Corynebacterium glutamicum towards increased malonyl-CoA availability for efficient synthesis of the plant pentaketide noreugenin - Lars Milke (Microbial Cell Factories, 2019)
Abstract Background In the last years, different biotechnologically relevant microorganisms have been engineered for the synthesis of plant polyphenols such as flavonoids and stilbenes. However, low intracellular availability of malonyl-CoA as essential precursor for most plant polyphenols of interest is regarded as the decisive bottleneck preventing high product titers. Results In this study, Corynebacterium glutamicum, which emerged as promising cell factory for plant polyphenol production, was tailored by rational metabolic engineering towards providing significantly more malonyl-CoA for product synthesis. This was achieved by improving carbon source uptake, transcriptional deregulation of accBC and accD1 encoding the two subunits of the acetyl-CoA carboxylase (ACC), reduced flux into the tricarboxylic acid (TCA) cycle, and elimination of anaplerotic carboxylation of pyruvate. The constructed strains were used for the synthesis of the pharmacologically interesting plant pentaketide noreugenin, which is produced by plants such as Aloe arborescens from five molecules of malonyl-CoA. In this context, accumulation of the C1/C6 cyclized intermediate 1-(2,4,6-trihydroxyphenyl)butane-1,3-dione (TPBD) was observed, which could be fully cyclized to the bicyclic product noreugenin by acidification. Conclusion The best strain C. glutamicum Nor2 C5 mufasO BCD1 PO6-iolT1 ∆pyc allowed for synthesis of 53.32 mg/L (0.278 mM) noreugenin in CGXII medium supplemented with casamino acids within 24 h.